The relevance of religious leaders in fostering an enduring democratic change agenda in Nigeria (2018)
Issues relating to expected roles of leaders generally in Nigeria have been discussed severally at various fora. But, an area where attention is yet to be focused on, is the aspect that has to do with the duties and responsibilities of religious leaders on matters affecting the political life of Nigerians, bearing in mind the high level of corruption, nepotism, favouritism, kidnapping, robbing Peter to Pay Paul syndrome and the menace of militant groups who have constituted themselves as clogs in the wheel of political development in our country. There is the need for the religious leaders to wake up from their slumbers and take the bull by the horn in order to find a lasting solution to the myriads of problems that have bedevilled the political structure in Nigeria. This is very important so that the change agenda of government will not be a mere wishful thinking. Therefore, the aim of this paper will be to examine the interconnectivity between religion and politics, the social responsibility of religion in the democratic change agenda and the role expected of religious leaders in Nigeria. Recommendations like the religious leaders being focused to their callings and others will also be made to address the seemingly insurmountable political problems in the country.